2016
DOI: 10.1515/pjvs-2016-0009
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and genetic analysis of a variant porcine epidemic diarrhea virus in China

Abstract: Porcine epidemic diarrhea virus (PEDV) is having a severe effect on the pig breeding industry in central China. The mucosa and the content of the small intestine from newborn pre-weaned piglets with diarrhea were tested for the presence of PEDV by molecular and morphologic methods, and found to be positive. Negative-staining electron microscopy (EM) revealed the presence of coronavirus-like particles in the samples. The result of molecular detection by nested RT-PCR based on the amplification of the M gene was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…Since the emergence of new PEDV strains in China in 2010, PEDV has continued to cause economic losses in almost all districts in the Hubei Province of China despite several control methods including biosecurity and vaccination. One important reason for this is the emergence of novel PEDV variants ( Jung and Saif, 2015 ; Li et al, 2016a ; Li et al, 2016b ). However, genetic information on PEDV in Hubei is quite limited; therefore, for better prevention and control of the spread of PEDV in the future, it is crucial to investigate the genetic diversity and variation of PEDV in fields.…”
Section: Discussionmentioning
confidence: 99%
“…Since the emergence of new PEDV strains in China in 2010, PEDV has continued to cause economic losses in almost all districts in the Hubei Province of China despite several control methods including biosecurity and vaccination. One important reason for this is the emergence of novel PEDV variants ( Jung and Saif, 2015 ; Li et al, 2016a ; Li et al, 2016b ). However, genetic information on PEDV in Hubei is quite limited; therefore, for better prevention and control of the spread of PEDV in the future, it is crucial to investigate the genetic diversity and variation of PEDV in fields.…”
Section: Discussionmentioning
confidence: 99%
“…According to researches, the PEDV is clustered into two groups: the classical PEDV strains that first emerged in 1970s in Europe and the highly virulent PEDV strains that emerged in 2010 in China [ 3 , 17 ]. The G1 PEDV strains are the classical PEDV, which can be clustered further into G1a where the prototype vaccine strain CV777 belongs; and G1b which includes new PED variants identified in South Korea, China, US and Europe [ 3 ].…”
Section: Resultsmentioning
confidence: 99%
“…Between 1971 and 1980, the virus reportedly spread rapidly in Europe and it was in 1982 when the first outbreak in Asia occurred that caused severe cases of diarrhea in neonate piglets that contributed to high mortality [ 3 ]. Several years later, the virus was reported in China [ 10 17 ], Japan [ 18 , 19 ], South Korea [ 20 22 ], Thailand [ 23 , 24 ], Vietnam [ 25 , 26 ] and the Philippines [ 5 , 27 ] (May 17, 2013, the United States Department). In May 17, 2013, the United States Department of Agriculture ( https://www.aphis.USDA2013.gov/animal_health/animal_dis_spec/swine/downloads/ped_tech_note.pdf ) National Veterinary Service Laboratory (NVSL) confirmed the first PEDV diagnosis in Iowa, United States [ 2 4 , 28 , 29 ] ( https://www.aphis.USDA2013.gov/animal_health/animal_dis_spec/swine/downloads/ped_tech_note.pdf ).…”
Section: Introductionmentioning
confidence: 99%
“…They were confirmed to be PEDV based on CPEs, IFA, EM, and RT-PCR results. An appropriate trypsin concentration and Vero cell line were essential for isolating PEDV in cell culture [ 8 13 ]. In this study, we found that ATCC-CCL81 Vero cells were more suitable for propagating field PEDV than were ATCC-1586 Vero cells, and 2 µg/mL trypsin at 37℃ for 1 h before inoculation into the Vero cells and medium containing 1 or 1.5 µg/mL crystalized trypsin were critical for propagating PEDV (data not shown).…”
Section: Discussionmentioning
confidence: 99%